José de la Cuadra, a Multifaceted Intellectual: Between Literature and Politics - Moret, Marlene (2020)
The Ecuadorian writer José de la Cuadra (Guayaquil, 1903-1941) has been consecrated for the art of his narrative. Nevertheless, few documents have drawn attention to the ideological complexity that can be traced in his works written outside of the literary realm. Here, the author studies three aspects of José de la Cuadra’s intellectual trajectory: first, the legacy of his social origins which facilitated his access to positions of power due to his work in Guayaquilean newspapers and magazines; then, the strategies he deployed to achieve recognition as a writer and intellectual at the national and international level; and finally, the contradictions he embraced as a militant socialist who went on to occupy political positions in non-democratic regimes.